Does globalization affect human development index? Evidence from high-corruption and low-corruption countries - Maichal, Maichal; Sugiyanto, Fransiscus Xaverius (Universitas Muhammadiyah Yogyakarta, 2025)
The impact of globalization on human development is widely debated, with corruption shaping whether its benefits are realized or undermined. While previous studies have typically examined globalization’s effects by classifying countries according to income level, development status, or regional grouping, little is known about how these effects differ across countries with varying degrees of corruption severity. This study examines how economic and social globalization influence the Human Development Index (HDI) in countries classified as low, moderate, and high corruption. Using panel data from 68 countries between 2005 and 2022, the analysis applies Fixed Effects, Random Effects, and Feasible Generalized Least Squares (FGLS). The most striking finding is that FDI has a negative and significant effect on HDI in low-corruption countries—many of which are advanced economies—contradicting conventional expectations that FDI fosters development under good governance. This result may reflect structural challenges such as aging populations, the refugee crisis, and geopolitical shocks that limit the developmental gains from foreign capital. By contrast, FDI shows no significant impact in moderate and high corruption countries, where weak institutions prevent investment benefits from being widely shared. Other results show that exports consistently enhance HDI across all corruption levels, imports matter only in moderately corrupt countries, internet access drives improvements in all groups, and tourism contributes positively only in high-corruption countries. The practical implication is that low-corruption countries must align FDI with demographic and labor-market strategies to ensure inclusive outcomes, while high and moderate corruption countries should strengthen institutions to unlock FDI’s potential.